1973
DOI: 10.1002/ardp.19733060306
|View full text |Cite
|
Sign up to set email alerts
|

Einwirkung von Gamma‐ und Neutronen‐Strahlung auf Arzneistoffe

Abstract: Gamma-und Neutronenstrahlung lost bei vielen Arzneistoffcn in wal3riger Losung Abbaureaktionen aus, die zu einer gr6fLeren Zahl von Folgeprodukten fuhren. Die Abnahme des Gehalts wuriger Losungen verlauft meist linear mit der eingestrahlten Dosis und ist unabhangig von der Dosisleistung der Strahlung. Ein Zusatz von NazSz05 ermoglicht meist keine wirksame Stabilisierung der Losungen gegeniiber ionisierender Strahlung. Bei der Gamma-und Neutronenbestrahlung von kristallinen Arzneistoffen, die oft zu einer Verfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The influence of ionising radiation on therapeutic drugs has been studied by many authors starting from the 1970s [2][3][4] . The first papers were devoted to comparisons of the effectiveness of ionising radiation and other methods of sterilisation, such as thermal or chemical sterilisation 5 and to establish the dose of irradiation that would be sufficient for the purpose 2,3,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…The influence of ionising radiation on therapeutic drugs has been studied by many authors starting from the 1970s [2][3][4] . The first papers were devoted to comparisons of the effectiveness of ionising radiation and other methods of sterilisation, such as thermal or chemical sterilisation 5 and to establish the dose of irradiation that would be sufficient for the purpose 2,3,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of ionizing radiation on the physicochemical properties of chloramphenicol was already studied [3][4][5][6][7][8][9][10]. The results proved that exposure to ionizing irradiation causes the appearance of radiolysis products, however, none of the authors of the hitherto published works identified all the radiolysis products and determined the safe dose of irradiation.…”
Section: Introductionmentioning
confidence: 99%